Conceptual model of low-cost improvised bubble continuous positive airway pressure device for adults and its potential use in the COVID-19 pandemic. - Himal Kharel; Zeni Kharel; Samikchhya Keshary Bhandari (PLoS Neglected Tropical Diseases)
Low-cost improvised continuous positive airway pressure (CPAP) device is safe and efficacious in neonatal respiratory distress. There is a great necessity for similar device in adults, and this has been especially made apparent by the recent Coronavirus Disease 2019 (COVID-19) pandemic, which is unmasking the deficiencies of healthcare system in several low-resource countries. We propose a simplified and inexpensive model of improvised CPAP in adults using locally available resources including aquarium air pumps and a novel pressure release mechanism. Although the safety and efficacy of improvised CPAP in adults are not established, the conceptual model we propose has the potential to serve as a lifesaving technology in many low-resource settings during this ongoing pandemic and thus calls for expedited research.